Type 2 lepra reaction in an immunocompromised patient precipitated by filariasis - Singh, Satyendra Kumar (Medknow Publications & Media Pvt Ltd, 2014)
Though patients affected with both acquired immuno deficiency syndrome (AIDS) and leprosy commonly present with type 1 lepra reaction, there are few isolated reports of type 2 lepra reaction in retropositive patients affected with leprosy. We are presenting a case report of 35-year-old male affected with AIDS, tubercular lymphadenitis, and lepromatous leprosy with recurrent episodes of type 2 lepra reaction manifesting as erythema nodosum leprosum (ENL). Dipstick enzyme-linked immunosorbent assay (ELISA) for filarial antigen was also positive. The patient was treated with 100 mg thalidomide daily, 300 mg diethylcarbamazine, and modified multidrug therapy (MDT) for leprosy. He responded well and has not had any further reaction in the last 6 months.